A proxy server management scheme for continuous media objects based on object partitioning - Seh Chul Park; Yong Woon Park; Yoo Ek Son (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
We propose a caching policy to service streams for continuous media objects over wide area networks. With the proposed policy, a group of proxy servers representing a tree-like structure are set per each local area network, providing as much transfer bandwidth as to service the expected maximum numbers of concurrent streams. Subsequently, two physical caches, the parent and each child cache, are combined and then treated as one logical cache. With this proxy server configuration, to reduce the initial latency taken to access the requested object from the central server and replacement overhead in the proxy server, each object is also logically partitioned into two parts (the front-end and rear-end partition) so as to cache as many front end partitions as possible; each partition of the objects is cached step by step in two phases. Finally, a new replacement policy is applied, where the recency, frequency and size of the requested objects are taken into consideration.